Memetic chicken swarm algorithm for job shop scheduling problem - Soukaina Cherif Bourki Semlali; Mohammed Essaid Riffi; Fayçal Chebihi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents a Memetic Chicken swarm optimization (MeCSO) to solve job shop scheduling problem (JSSP). The aim is to find a better solution which minimizes the maximum of the completion time also called Makespan. In this paper, we adapt the chicken swarm algorithm which take into consideration the hierarchical order of chicken swarm while seeking for food. Moreover, we integrate 2-opt method to improve the movement of the rooster. The new algorithm is applied on some instances of ORLibrary. The empirical results show the forcefulness of MeCSO comparing to other metaheuristics from literature in term of run time and quality of solution.